BAHASA PADA BEGALAN DALAM ADAT PERNIKAHAN BANYUMAS - Suwartono Suwartono (University of Muhammadiyah Purwokerto, 2007)
This study dealt with the philosophy behind the Banyumas traditional wedding ceremony of Begalan. The aims of the study were (1) to classify the main ideas or themes delivered in the cultural event and (2) to identify linguistic items used in the cultural event in relation with the Banyumas people's cultural characteristics. The research data were collected through observation and interviews. Notes were taken, and the traditional ceremony performers' speech and source person's interviews were recorded. Data were analyzed through coding and classifying procedures. For data validation triangulation was also conducted. The research results have shown that (1) there are, at least, •2 main ideas or themes delivered in the cultural event of Begalan, i.e: the aim of conducting the traditional wedding ceremony and the philosophy behind the cultural artifacts that were made available in the ceremony. The philosophy consists of wishes that the newly-built family not go through stormy days; (2) the adoption and adaptation of words from other languages or outside Banyumas dialect Javanese indicates the adaptability of Banyumas people toward other cultures, and the use of relatively rude words, the expression of impolite intentions and the porno-oriented actions in public reflect the frankness or straightforwardness of this kind of people.